A Preliminary Study on the Removal of Methylene Blue from Aqueous Solution using Moringa Pods as Bioadsorbent under Column Operation - Rodríguez, Mirla; Flores, Saúl; Argotte, Alexandra (Journal of Applied Solution Chemistry and Modeling, 2017)
Moringa pods (MP) was used as bioadsorbent to remove methylene blue (MB) from aqueous solutions under fixed-bed column operation. The bioadsorbent was analyzed by Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). Surface area (Brunauer-Emmet-Teller) and point of zero charge (pHPZC) were determined. In this study, pH influence (2.0 to 10.0) was evaluated, keeping constant conditions of bed height (11.0 cm), bioadsorbent dose (2.0 g), dye concentration (20 mg L-1), volume (25 mL), contact time (24 h) and room temperature. The MB concentration was determined using UV-spectrophotometry at 662 nm. The results showed that the adsorption was pH dependent. The highest dye removal occurs at pH 7.0 (Ëœ100%). Infrared spectrum and morphological changes observed by SEM indicate the existence of bioadsorption phenomenon. An adsorption mechanism possible by intermolecular interactions was proposed. The study revealed the applicability of MP for removal of MB at low cost, efficient, eco-friendly and relatively neutral pH.